A new species of Kalophrynus (Amphibia, Anura, Microhylidae) from Southern Peninsular Malaysia - Matsui, Masafumi; Nishikawa, Kanto; Belabut, Daicus M.; Norhayati, Ahmad; Yong, Hoi Sen (Zootaxa, 2012)
A new microhylid, Kalophrynus limbooliati sp. nov., is described from the state of Johor, in the southern part of PeninsularMalaysia. Morphologically, the new species differs from all known congeners in the combination of medium body size;short fourth finger; two subarticular tubercles on fourth finger and none on the fifth toe; presence of light lateral stripe anddark inguinal spot; absence of nuptial pads and outer metatarsal tubercles. Acoustically, the new species clearly differsfrom all congeners whose calls have been reported, and resembles a syntopic ranid Hylarana laterimaculata with a long series of high-pitched whistle like notes.